2021
DOI: 10.1186/s12891-021-04357-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of fibrinogen in predicting reinfection after DAIR for periprosthetic joint infections

Abstract: Background Fibrinogen (FIB) has been found to be a promising marker in diagnosing periprosthetic joint infection (PJI), however, the value of FIB in predicting reinfection of PJI is unknown. The purpose of this study was to evaluate the value of FIB in predicting reinfection after debridement, antibiotics, and implant retention (DAIR) for PJI. Methods We retrospectively analyzed the clinical data of patients who were diagnosed with PJI and underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…[ 13 ] used DABRI for the first time for the treatment of acute knee PJIs. Two patients failed to respond due to methicillin-resistant Staphylococcus aureus infection, even though the level of C-reactive protein after 30 days of treatment decreased in both cases [ 37 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] used DABRI for the first time for the treatment of acute knee PJIs. Two patients failed to respond due to methicillin-resistant Staphylococcus aureus infection, even though the level of C-reactive protein after 30 days of treatment decreased in both cases [ 37 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…FIB is also an efficient biomarker for the detection of infection in patients with non-union of fractures after internal fixation, showing a sensitivity of 78.2% and a specificity of 82.4% at an optimal cutoff of 2.75 g/L [28] . In addition, FIB also is promising for predicting reinfection after debridement, antibiotics, and implant retention for both acute and chronic PJI, and it may perform better than CRP and ESR [29] . And it is also promising for screening PJI prior to revision arthroplasty in patients without inflammatory diseases [19,30] .…”
Section: Discussionmentioning
confidence: 99%
“…[28] In addition, FIB also is promising for predicting reinfection after debridement, antibiotics, and implant retention for both acute and chronic PJI, and it may perform better than CRP and ESR. [29] And it is also promising for screening PJI prior to revision arthroplasty in patients without inflammatory diseases. [19,30] The optimal cutoff values reported in those studies were 3.57 and 4.01 mg/L, respectively, and our study revealed that plasma FIB may be useful at an optimal cutoff of 4.04 mg/L for screening PJI in patients with inflammatory diseases subjected to revision arthroplasty.…”
Section: Discussionmentioning
confidence: 99%